Aid effectiveness in the health sector - Melisa Martínez Álvarez; Arnab Acharya (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This paper explores the current evidence underlying the debate on aid effectiveness, with a specific focus on the health sector. It summarizes the history of aid and outlines the methodological challenges encountered when assessing its effectiveness. The current evidence on 'what works' in the different aid modalities is outlined, highlighting examples of success. The review finds that resource allocation, lack of predictability of funds, fragmentation, fungibility and the system of relationships foreign aid generates all hinder its effectiveness. Furthermore, even when projects are successful, countries face constraints in scaling them up. The aid effectiveness debate is dynamic, however, and constantly influenced by new global policies and players. The paper ends with a discussion of the future of aid and how these new actors and policies are likely to shape the landscape of development co-operation.
Keywords: O10; O16; O19; 330; aid effectiveness; health; fungibility; harmonization; Entwicklungshilfe; Gesundheitswesen